Student evaluation of university teaching : a case study in Nanyang Technological University - Sim, Gim Hoon (2008)
This research attempts to look into the effectiveness of student's evaluation feedback form as a measurement of university teaching. A local study was conducted based on a random sample of students and teachers from the school of Accountancy and Business in NTU.